Optimizing the parameters in durian skin fiber reinforcedpolypropylene composites by response surface methodology - Anuar, Hazleen; Aimi, N. Nur; Manshor, M.R.; Wan Nazri, W.B.; Mohd Salit, Sapuan (Elsevier, 2014)
tAwareness on the advantages of natural fibers stimulates the interest of researchers to use them asreinforcement in polymer composites for robust application. Therefore, investigation on optimizing theimpact property of durian skin fiber (DSF) reinforced polypropylene (PP) composites was carried outto determine the effect of DSF content, fiber size and maleic anhydride polypropylene (MAPP) content.Response surface methodology (RSM) was used in the design of experiments and in the analysis of results.The optimized value for the maximum impact strength of PP–DSF composite was found at 50 wt% DSFcontent and fiber size range of 250–500 m with 0 wt% MAPP. The maximum impact property for PP–DSFcomposite was 10.66 kJ/m2. From the analysis of variance (ANOVA), fiber content significantly affects thestrength of PP–DSF composites, followed by the fiber size and MAPP content. The P-value of the modelof experiment is less than 0.05 and the determination coefficient (R2) is nearly 1 which suggested thatthe model is significant and implies on the precision and processability in the production.